Enhancing Students’ Active Involvement, Motivation and Learning Outcomes on Mathematical Problem Using Problem-Based Learning - Lisya Yulia Sari; M. Fachri Adnan; Hadiyanto Hadiyanto (Postgraduate School, Universitas Negeri Padang, 2019)
The rationale of this study was based on the problems experienced by the researcher especially in teaching mathematics. Students faced some difficulties in understanding and solving math problems especially the questions presented in stories; as a result, their learning outcomes were low. These difficulties were seen in the learning process in which the students were not active in learning. They were also ignorant, noisy and bored during a learning process. In the primary study, it has been predicted that this would happen due to the conventional way of teaching which is lecturing. Hence, the students’ active involvement in the class was low, and they were less motivated in learning. Problem Based Learning (PBL) learning model is one solution that can be used to enhance students’ active involvement, motivation and learning outcomes. This study was Classroom Action Research (CAR) which consisted of 2 cycles in which each cycle consisted of 2 meetings. Each cycle had three stages, namely the planning stage, the implementation and observation stages, and the reflection stage. At the observation stage, the researcher was assisted by observers who were observing and recording students’ activity and learning motivation. In brief, the results revealed that after implementing of PBL model of learning, there was an improvement in students’ activity, motivation and learning outcomes from one cycle to the next.